Aliphatic Biomakerof Crude Oil from Juwata, Tarakan, North Kalimantan - Endah Mutiara Marhaeni Putri; Eduardus Edi; R. Y. Perry Burhan; Yulfi Zetra; Agus Wahyudi; Zjahra Vianita (IPTEK Journal of Proceedings Series, 2017)
Characteristic organic geochemistry of crude oil Juwata, Tarakan, North Kalimantan provide information about the depositional sedimental environment and maturity of the oil. Crude oil was extracted with n-hexane (50: 2) for 24 hours to separate the crude oil with asphaltene, and if precipitation does not separate perfectly then centrifuged. Extracts were then refractionated using column chromatography according to the methods McCharty base. Fractionation results are obtained in the form of the neutral fraction, the acid fraction and polar fraction. Neutral fraction separated with KLTP method and aliphatic fraction and aromatic fractions. Aliphatic fraction subsequently analyzed by GC-MS. GC-MS analysis aliphatic fraction of n-alkanes in the form of compounds, and hopane, bikadinancompounds. The pattern of distribution of n-alkanes which consists of a range of C-17 to C-33. Carbon distribution with a range of C-21 to C-33 is dominating compared to the C-17 to C-20. This distribution pattern indicates the source of organic matter from terrestrial land wax component derived from higher plants. Hopane presence of compounds in crude oil aliphatic fractionsJuwata Tarakan, North Kalimantan analyzed by fragmentogram m/z = 191. Hopane biomarker provide that information during the sedimentation stage diagenesis these compounds are degraded and stereochemical changes towards a stable isomer form, configuration changes 17α (H), 21β (H) during the process of diagenesis to a stable isomer which is 17 α (H), 21β (H) or 21β (H), 17 α (H) indicates that oil comes from the old sediments. Biomarka bikadina identified according fragmentogram m/z = 191 multiple ion fragment m/z = 109.191, 369, 397 and ion molecular m/z = 412 showed the characteristic fragment bikadinna compound. Biomarka bikadina give information influx of organic material terrestrial region. The compounds showed crude oils biomarker Juwata Tarakan, North Kalimantan derived from terrestrial depositional environments.